2016
DOI: 10.4236/jmp.2016.73028
|View full text |Cite
|
Sign up to set email alerts
|

Invariants in Relativistic MHD Turbulence

Abstract: The objective of this work is to understand how the characteristics of relativistic MHD turbulence may differ from those of nonrelativistic MHD turbulence. We accomplish this by studying the ideal invariants in the relativistic case and comparing them to what we know of nonrelativistic turbulence. Although much work has been done to understand the dynamics of nonrelativistic systems (mostly for ideal incompressible fluids), there is minimal literature explicitly describing the dynamics of relativistic MHD turb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The situation is somewhat different in the case of relativistic compressible theory. The initial studies of relativistic MHD turbulence (see Zhang, MacFadyen, and Wang, 2009;Inoue, Asano, and Ioka, 2011;Beckwith and Stone, 2011;MacFadyen, 2012, 2013;Garrison and Nguyen, 2015) have not revealed much differences between the non-relativistic and relativistic turbulence. However, more recent studies in Lazarian (2016, 2017) provided the decomposition of the turbulent motions into Alfven, slow and fast modes.…”
Section: Relativistic Mhd Turbulencementioning
confidence: 99%
“…The situation is somewhat different in the case of relativistic compressible theory. The initial studies of relativistic MHD turbulence (see Zhang, MacFadyen, and Wang, 2009;Inoue, Asano, and Ioka, 2011;Beckwith and Stone, 2011;MacFadyen, 2012, 2013;Garrison and Nguyen, 2015) have not revealed much differences between the non-relativistic and relativistic turbulence. However, more recent studies in Lazarian (2016, 2017) provided the decomposition of the turbulent motions into Alfven, slow and fast modes.…”
Section: Relativistic Mhd Turbulencementioning
confidence: 99%
“…Fully relativistic MHD turbulence has been studied since 2009 (Zhang et al (2009); Inoue et al (2011); Beckwith and Stone (2011); MacFadyen (2012, 2013); Garrison and Nguyen (2015), see also Radice and Rezzolla (2013) for non-magnetized turbulence). The results in MacFadyen (2012, 2013) for the mean lab-frame Lorentz factor of ∼1.67 and numerical resolutions of up to 2048 3 confirm that there exists an inertial sub-range of relativistic velocity fluctuations with a -5/3 spectral index.…”
Section: Fully Relativistic Mhd Turbulencementioning
confidence: 99%
“…This relativistic analog of GS95 was successfully tested for the case of decaying turbulence in Cho (2005) under the so-called force-free approximation. 3 The simulations of fully relativistic MHD turbulence (Zhang et al, 2009;Inoue et al, 2011;Beckwith and Stone, 2011;Zrake & MacFadyen, 2012Garrison & Nguyen, 2015) delivered results also consistent with the GS95 expectations. Recent studies of compressible relativistic MHD turbulence in Takamoto & Lazarian (2016 revealed the difference between it and its non-relativistic analog (see Cho & Lazarian 2002, Kowal & Lazarian 2010.…”
Section: Magnetic Reconnection In Relativistic and Strongly Magnetizementioning
confidence: 56%